Improving processes in long-term care - Lindo, Maria Leonor Sá Quental de Melo (2018)
Process improvement applied in healthcare is a subject that is reaching a large dimension over the years. Increasingly companies need to stay competitive and differentiate themselves from each other. Lean as process improvement arises as a solution to improve core processes and to gain competitiveness. In the healthcare area, arises as a cost reduction solution in the health sector and allows the rationalization of resources and a better practice of all processes inherent to the provision of the service, making the service an added value for the customer. This dissertation aims to identify how can process improvement add value to the long-term care services, under the application of process improvement, namely Lean Thinking tools. Furthermore, a theoretical framework is provided in order to support the current investigation. A methodology of dissertation with a case study is applied to the long-term care, namely in medium-term and rehabilitation care, in Santa Casa da Misericórdia de Alhos Vedros unit where direct observation, focus group and informal interview are performed with stakeholders of the service. Value stream mapping and flowchart are applied to the process of medium-term and rehabilitation care. The customers of this service are identified as well as what is their value perception of service. Value-stream mapping allows to identify sources of waste, and possible improvement suggestions are presented. The outcome of this research allows to improve the medium-term and rehabilitation process and consequently the service delivery, making the process more efficient.